2022
DOI: 10.3390/jfb13030153
|View full text |Cite
|
Sign up to set email alerts
|

Primary Teeth-Derived Demineralized Dentin Matrix Autograft for Unilateral Maxillary Alveolar Cleft during Mixed Dentition

Abstract: This clinical report describes the immediate autograft of primary (milk) teeth-derived demineralized dentin matrix (DDM) granules for a 6-year-old boy with unilateral alveolar cleft. First, four primary teeth were extracted, crushed in an electric mill for 1 min, and the crushed granules were demineralized in 2% HNO3 solution for 20 min. Simultaneously, the nasal mucoperiosteum was pushed upwards above the apices of the permanent central incisor adjacent to the cleft. The nasal and palatal openings were closed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Experimental in vivo studies have validated the biological performance of ADTM granules for bone healing. Several studies on the transplantation of human dentin blocks into human bone defects have shown noticeable intimate contacts without soft tissue that reveal progressive dentin-bone ankylosis after 6 months, and then replacement by bone tissue without any inflammatory reactions [58][59][60]. Thus, the feasibility of a clinical procedure with ATDM granules associated with their bone response has been receiving attention by scientists and clinicians [2,35,60].…”
Section: In Vivo Evidence Of Bone Healingmentioning
confidence: 99%
“…Experimental in vivo studies have validated the biological performance of ADTM granules for bone healing. Several studies on the transplantation of human dentin blocks into human bone defects have shown noticeable intimate contacts without soft tissue that reveal progressive dentin-bone ankylosis after 6 months, and then replacement by bone tissue without any inflammatory reactions [58][59][60]. Thus, the feasibility of a clinical procedure with ATDM granules associated with their bone response has been receiving attention by scientists and clinicians [2,35,60].…”
Section: In Vivo Evidence Of Bone Healingmentioning
confidence: 99%